2004
DOI: 10.1139/z04-187
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal characteristics of swift foxes

Abstract: From 1997 to 2001, we monitored movements of 109 adult and 114 juvenile swift foxes, Vulpes velox (Say, 1823), at study sites in Colorado, New Mexico, and Texas to determine patterns of dispersal. Significantly more male (93%) than female (58%) juveniles dispersed, and both sexes had similar bimodal dispersal patterns with peaks in September–October and January–February. Adult dispersal occurred more evenly throughout the year, and significantly more male (32%) than female (5%) adults dispersed. Adult males te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
6
21
1
Order By: Relevance
“…Thus, the individuals most likely to engage in close inbreeding would be the most successful males and their daughters. For these males, secondary dispersal might provide a means to reduce the likelihood of mating with a daughter, such as that observed in swift foxes (Vulpes velox; Kamler et al 2004); however, we found no evidence of males abandoning their established home ranges after the age of six years (Costello 2008).…”
Section: Discussionsupporting
confidence: 53%
“…Thus, the individuals most likely to engage in close inbreeding would be the most successful males and their daughters. For these males, secondary dispersal might provide a means to reduce the likelihood of mating with a daughter, such as that observed in swift foxes (Vulpes velox; Kamler et al 2004); however, we found no evidence of males abandoning their established home ranges after the age of six years (Costello 2008).…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, although frequent dispersal of adult males was reported in other fox species (Kamler et al. ,b), the frequent dispersal of adult females is unusual among canids in particular, and mammals in general. The dispersal patterns of bat‐eared foxes may be related to their unique evolutionary lineage (Maas and Macdonald ).…”
Section: Discussionmentioning
confidence: 93%
“…), including other fox species (Macdonald and Courtenay ; Kamler et al. ). Although sample size was too low for significance, males dispersed farther, on average, on Benfontein than PR.…”
Section: Discussionmentioning
confidence: 99%
“…First, juveniles often remained spatially affiliated with adults for several weeks or months beyond the pup‐rearing season, though observed philopatry was highly variable (B. M. Kluever, unpublished data ), as has been observed in other canid investigations (Kamler et al. , Gosselink et al. ), But, when juveniles foxes did ultimately fully engage in dispersal behavior, they were likely faced with the challenge of locating areas containing suitable resources; it is intuitive that such forays would depress den use residency.…”
Section: Discussionmentioning
confidence: 91%
“…This finding may be attributed to several factors. First, juveniles often remained spatially affiliated with adults for several weeks or months beyond the pup-rearing season, though observed philopatry was highly variable (B. M. Kluever, unpublished data), as has been observed in other canid investigations (Kamler et al 2004, Gosselink et al 2010, But, when juveniles foxes did ultimately fully engage in dispersal behavior, they were likely faced with the challenge of locating areas containing suitable resources; it is intuitive that such forays would depress den use residency. Finally, in the system we investigated survival probability for juvenile foxes is markedly less than that of adults (Kluever and Gese 2017) and this likely influenced expected weekly residency times for this age class; an animal cannot re-use the same den if it has expired.…”
Section: Discussionmentioning
confidence: 96%